The The Correlation of Personal Hygiene Behavior on The Incidence of Dandruff (Pityriasis sicca) in Adolescents Living in Orphanages in Kelapa Lima Sub-District, Kupang City - Veronica .; Sangguana Marthen Jacobus Koamesah; Regina Marvina Hutasoit; Conrad Liab Hendricson Folamauk (Universitas Nusa Cendana, 2025)
Background: Dandruff is a condition of exfoliation of the corneum layer of the scalp forming white flakes, which is most common in adolescents because the sebaceous glands actively produce sebum causing increased colonization of Malassezia sp. yeast, the cause of dandruff. A factor that influences the incidence of dandruff is personal hygiene behavior. Adolescents in orphanages have a high risk of experiencing dandruff due to poor personal hygiene behavior, one of which is the use of personal items alternating to fellow friends. Objective: To determine whether there is a correlation between personal hygiene behavior and the incidence of dandruff (Pityriasis sicca) in adolescents living in orphanages in Kelapa Lima Sub-District, Kupang City. Methods: This study used an observational analytic research design with a cross-sectional study design. Respondents were selected by purposive sampling method according to the inclusion and exclusion criteria by taking the minimum number of respondents using the Lemeshow formula so that 55 respondents were obtained. Data collection using personal hygiene behavior questionnaire and wood lamp inspection. Data analysis using the fisher exact test. Results: The correlation between personal hygiene behavior and the incidence of dandruff obtained p-value = 0.223 (p>0.05) with fisher exact test, so it does not have a significant correlation. Two items of personal hygiene behavior on the questionnaire, namely the use of sleeping pillows alone / changing with others has a p-value = 0.007 (p < 0.05), and shampooing after completing outdoor activities and long-term exposure to polluting dust has a p-value = 0.016, so it has a significant correlation with the incidence of dandruff. Conclusion: There is no significant correlation between personal hygiene behavior and the incidence of dandruff in adolescents living in orphanages in Kelapa Lima District, Kupang City.